Mechanism and relevance of necroptosis to immune microenvironment of periodontitis: A pilot study - ZHENG Zhanglong; LI Jia; JIANG Jirui; SHAN Zhengnan; LI Shengjiao (Kouqiang hemian waike zazhi)
[Objective:] To explore the effect and mechanism of necroptosis on the immune microenvironment of periodontitis. [Methods:] We screened out the differentially expressed necroptosis-related genes in periodontitis, first calculated the hub genes through machine learning algorithms, and constructed a diagnostic model. Then the relative abundance of immune cells in the periodontitis and healthy groups was analyzed and its correlation with necroptosis-related genes was calculated. Collect healthy and inflammatory gingival tissues from individuals and extract RNA, then validate the inter-group expression level of necroptosis-related genes using real-time quantitative polymerase chain reaction (RT-qPCR). [Results:] A total of 10 necroptosis-related genes were differentially expressed, including 8 hub genes. Compared with healthy tissues, the relative infiltration of plasma cells, B cells, neutrophils and NK cells in periodontal inflammatory tissues were increased. The relative infiltration of macrophages and resting dendritic cells decreased. Among them, absent in melanoma 2 (AIM2), mixed lineage kinase domain like pseudokinase (MLKL) were significantly positively correlated with the expression of plasma cells. [Conclusion:] Necroptosis affects the immune microenvironment of periodontitis.